Penerapan Pendidikan Agama Islam pada Keluarga Millenial - Nur Khamim (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2019)
Religious education is one of the determinants of the future for every individual. Religious education is the foundation of behavior for individuals because religion is related to the beliefs possessed by the individual. Human behavior in millennial times is easily influenced by the environment. Millennial era marked by the use of social media in various aspects of life makes it easier for the environment to influence individual behavior. The development of modern technology makes the lifestyle more modern, with this situation the process of religious education in millennial families needs to be re-understood to be able to produce religious education that remains optimal. This research was conducted by qualitative methods to millennial families in Gresik district. The results showed that millennial parents showed efforts to provide religious education to children with formal education in madrasas and practical religious education by parents. The ability of children regarding education in millennial families is emphasized in the discipline in carrying out compulsory prayer, fasting and good morals. As millennial families the main obstacle in implementing Islamic religious education in children, the presence of gadgets becomes an obstacle because when children play it is easy to forget the time